If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12n + 6 = 3r + -1(-7d) Reorder the terms: 6 + 12n = 3r + -1(-7d) Remove parenthesis around (-7d) 6 + 12n = 3r + -1 * -7d Multiply -1 * -7 6 + 12n = 3r + 7d Reorder the terms: 6 + 12n = 7d + 3r Solving 6 + 12n = 7d + 3r Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 12n = 7d + -6 + 3r Combine like terms: 6 + -6 = 0 0 + 12n = 7d + -6 + 3r 12n = 7d + -6 + 3r Reorder the terms: 12n = -6 + 7d + 3r Divide each side by '12'. n = -0.5 + 0.5833333333d + 0.25r Simplifying n = -0.5 + 0.5833333333d + 0.25r
| -7v+4(v-7)=-1 | | -3(1+n)=29+n | | 13*4=x*5 | | 2x+8=19/2 | | 4x=2 | | 4(u+4)-6u=2 | | (x+2)=2y-1 | | x-5=7 | | x-10=-8 | | 5y+22=7(y+4) | | 4x+21=25 | | 4(u+4)-u=2 | | 4(4x-3)-6x= | | (3(4))= | | 6x+18=2x+6 | | 155=5(6+5x) | | 8x-2(x-5)=x | | 8x-2(x-5)=x+12 | | -16=-8u+6(u-4) | | 8.6e+12= | | x^2+30x+144=0 | | -12=3(w+2)-6w | | -4y+7=-10+37 | | 26=3(x+7)-8x | | x+8=68 | | 12-3/5x-1/5x=16 | | 5a+12a-6b+4a= | | 40-7x=2x+17 | | 11+15w=-7+13x | | -33=3(y-5)-5y | | 16=2+38t-16t^2 | | 2(w+3)-7w=26 |